Xenoandrogenic activity in serum differs across European and inuit populations - Kruger T; Hjelmborg PS; Jonsson BA; Hagmar L; Giwercman A; MANICARDI, Gian Carlo; Bizzaro D; Spano M; Rignell Hydbom A; Pedersen HS; Toft G; Bonde JP; et al. (Environmental Health Perspectives, 2007)
Background: Animal and in vitro studies have indicated that human male reproductive disorders can arise as a result of disrupted androgen receptor (AR) signalling by persistent organic pollutants (POPs) . Our aim in the present study was to compare serum xenoandrogenic activity between study groups with different POP exposures and to evaluate correlations to the POP proxy markers 2,2 ́,4,4 ́,5,5 ́-hexachlorobiphenyl (CB-153) and 1,1-dichloro-2,2-bis(p-chlorophenyl) -ethylene (p,p ́-DDE) .Methods: We determined xenoandrogenic activity in the serum fraction containing the lipophilic POPs but free of endogenous hormones. Adult male serum (n = 261) from Greenland, Sweden, Warsaw (Poland) , and Kharkiv (Ukraine) was analyzed. Xenoandrogenic activity was determined as the effect of serum extract alone (XAR) and in the presence of the synthetic AR agonist R1881 (XARcomp) on AR transactivated luciferase activity.Results: The study groups differed significantly with respect to XARcomp activity, which was increased in the Inuits and decreased in the European study groups we observed no difference for XAR activity. We found the highest level of the AR antagonist p,p ́-DDE in Kharkiv, and accordingly, this study group showed the highest percent of serum samples with decreased XARcomp activities. Furthermore, the percentage of serum samples with decreased XARcomp activities followed the p,p ́-DDE serum level for the European study groups. No correlations between serum XAR or XARcomp activities and the two POP markers were revealed.Conclusions: The differences in XARcomp serum activity between the study groups suggest differences in chemical exposure profiles, genetics, and/or lifestyle factors.